Evaluation of Grounding System Maintenance at JIS Jakarta School Building - Gunawan, Agus; Sidik, Darmawan; Gultom, Arlewes (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research analyzes the maintenance of the grounding system in JIS Pattimura School Building, Jakarta, to improve electrical safety and reliability. A reliable grounding system protects equipment and people from electrical hazards. The research methods include observation, measurement of grounding resistance with an Earth Tester, and analysis based on PUIL standards. The results show that some grounding points, such as the grounding on the server panel and alarm panel, require improvement because the resistance value exceeds the standard, especially in areas with dry soil or covered by buildings, with the grounding resistance value after improvement of 0.96 Ohm and 1.09 Ohm, respectively. The solution implemented was the addition and deepening of grounding electrodes to lower the resistance. Regular maintenance and periodic monitoring are recommended. A maintained grounding system improves safety, extends equipment life, and ensures compliance with standards.